PENGARUH PENAMBAHAN FEED ADITIF DALAM RANSUM DENGAN DOSIS YANG BERBEDA TERHADAP BOBOT TELUR DAN NILAI HAUGH UNIT (HU) TELUR AYAM RAS - Destama Rendy Saputra; Tintin Kurtini; Erwanto . (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
This research aims to 1) study the effect of using feed additive on ration for egg weight and haugh unit (HU) value; 2) study optimum doses of feed additive in ration layer. This research was conducted in May - June 2016 at layer farm in Sumber Sari, Tamansari village of Gedong Tataan, Pesawaran, Analysis Laboratory Polytechnic of Lampung, Laboratory of Nutrition and Food livestock, and Laboratory Production and Reproduction of Livestock  Animal Husbandry Department, Faculty of Agriculture, University of Lampung.  This  research used completely randomized design with 4 treatments of feed additives doses (0; 0.15; 0.25; and 0.35%) added on feed with 5 replications. Each replications using four layer. The data were analyzed using ANOVA analysis with 5% significance level. Significantly different results was further tested by orthogonal polynomials. The result can be conclude that 1) Addition of feed additives with a doses of 0; 0.15; 0.25; 0.35% on feed influence insignificantly (P> 0.05) to the egg weight, but it influenced significantly (P<0.05) in the Haugh unit value (HU). 2) The optimum dose addition of feed additives in the ration was 0.24% on the value of Haugh units of eggs. Keywords: Feed Additive, Egg Weight, Haugh Unit Value, Layer